2 years ago


Answers : (2)


Are of the cure is the integral of the graph function

2 years ago

The area under the plot of plasma concentration of drug (not logarithm of the concentration) against time after drug administration. The area is conveniently determined by the “trapezoidal rule”: the data points are connected by straight line segments, perpendiculars are erected from the abscissa to each data point, and the sum of the areas of the triangles and trapezoids so constructed is computed. When the last measured concentration (Cn, at time tn) is not zero, the AUC from tn to infinite time is estimated by Cn/kel.

2 years ago

Post Your Answer

More Questions On Integral Calculus

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
help help.......
Ans: Hello Student, Please find answer to the following question is a one-one function. So which means that every input has only one output. Given: Since only one statement is correct and...
Jitender Singh one month ago
evaluate ∫ (sqrt(x)( ax^2 + bx + c)) dx
∫ (sqrt(x)( ax^2 + bx + c)dx =​∫ (x^1/2(ax^2 +bx +c)dx =​∫ (ax^5/2 +bx^3/2 +cx^1/2)dx =2​ax^7/2 /7 +2bx^5/2 /5 +2cx^3/2 /3 +K {we know that​∫x^ndx =(x^(n+1) /(n+1)} Here K is...
Sunil Raikwar 2 months ago
make ax 2 +bx+c in to form of a((x-b/2) 2 +(c -b 2 /4)). then put (x-b/2)=(c-b 2 /4)^.5*tany. then integrate it. simple
Karthick vel 2 months ago
please help anyone please
Nishant Vora one month ago
prove that n 3 + 3n 2 + 5n + 3 is divisible by 3 for any natural number n
Hello Student, n^3 + 3n^2 + 5n + 3 =n^3 + 3n^2 + 2n+3n + 3 =n(n^2 + 3n + 2)+3n + 3 =n(n+1)(n+2)+3n+3 Prooved Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
Arun Kumar 3 months ago
By Fermat’s theorem, n 3 -n is divisible by 3. Hence n 3 +3n 2 +5n+3 = (n 3 -n)+(3n 2 +6n+3) = 3m+3(n+1) 2 for some integer m making the expression obviously a multiple of 3.
mycroft holmes 3 months ago
m=2-(3)^(1/2) Find the value of (m^6+m^5+m^4+1)/m^3
Hello student, This may help you m = 2 – 3^(1/2), and rationalising this we get m + 1/m = 4. som^2 = 4m-1 Given equation is= (m^3+1/m^3) +m^2+m From the identity if a+b+c = 0 gives...
Hello student, Please find the answer to your question below as m= m 2 =7- m 3 =26-15 1/m 3 =26+15 Given (m 6 +m 5 +m 4 +1)/m 3 =m+m 2+ m 3 +1/m 3 =2- +7-4 +26-15 +26+15 =61-5
m = 2 – 3^(1/2), and so m + 1/m = 4. We can also write this last equation as m^2 = 4m-1 Given expression = (m^3+1/m^3) +m^2+m Now, using the identity: a+b+c = 0 implies a^3+b^3+c^3 = 3abc,...
mycroft holmes 2 months ago
what is the value of
This can be solved using expansion of sin -1 x and tan -1 x which follows sin^(-1)x=x+1/6x^3+ 3/(40)x^5+5/(112)x^7+(35)/(1152)x^9+... tan^(-1)x=x - 1/3x^3 + 1/5x^5 – 1/7x^7+... When...
Harsh Patodia 24 days ago
View all Questions »